Assessing Indoor air quality and sick building syndrome in public University buildings: a cross-sectional study of office worker health and well-being - Mohd Fairus Awang,; Roslena Md Zaini,; Nasrul Amir Abdul,; Mohd Rohaizat Mat Tahir,; Aida Baharuddin,; Siti Nurul Hunadia Husin,; Nooraini Ahmad@Zakaria,; Nik Lukman Nik Ibrahim,; Haris Hafizal Abd Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Exposure to indoor air pollution among office workers can result in various health issues and increase the incidence of Sick Building Syndrome (SBS). The aim of the present study was to investigate the effect of exposure to Indoor Air Quality (IAQ) among office workers and the relationship with the prevalence of SBS at Universiti Kebangsaan Malaysia (UKM), Bangi. A cross-sectional comparison research involving 144 office workers from various new and old buildings was carried out at UKM, Bangi. Information was gathered and symptoms associated with SBS were determined using a series of questionnaires. During office hours, IAQ parameters were collected using air quality sensor. The old building had substantially higher levels of NO2 (24.26 ppb), CO (0.62 ppb), and PM10 (4.99 μg/m3) than the new building. It was found that, with a p < 0.001, the concentration of O3 in the new building (11.47 ppb) was significantly higher than in the old building (4.93 ppb). The study’s findings also showed that the difference in temperature between the old buildings (26°C) and new buildings (24°C) was statistically significant (p = 0.003). Referring to relative humidity (RH), the result of the old building is lower (56%) compared to the new building (62%). Although old buildings exhibited a higher prevalence of SBS (34.7%), it was found that there was no significant difference compared to new buildings (27.5%). According to the study’s findings, found that exposure to CO (χ2 = 5.242, p = 0.022), PM10 (χ2 = 13.449, p < 0.001), and PM2.5 (χ2 = 19.755, p < 0.001) among office workers with the prevalence of SBS has significant association. In conclusion, this study suggests that exposure to high levels of CO, PM10 and PM2.5 can increase the prevalence of SBS. Good housekeeping and regular maintenance of ventilation can keep good IAQ and reduce health effects among occupants.